How Students Develop Skill and Identity in an Agricultural Communications Writing Course - Holli R. Leggette; Holly Jarvis (Journal of Applied Communications, 2015)
Writing is more than a means of communication. It is one way students can gain knowledge and develop their personal and professional identity. The purpose of this study was to understand students’ perspectives on how they developed skill and identity as writers in an agricultural communications writing course. Fifteen students wrote one-page student reflections about their experience in Agricultural Media Writing I. The reflections were analyzed using a qualitative content analysis, which was guided by the seven vectors identified in Chickering and Reisser’s (1993) theory of education and identity. After analyzing the one-page reflections, the data f it vectors one, two, three, four, five, and six but did not fit vector seven. College students in this course developed competence, the ability to manage their emotions, a balance between autonomy and independence, intimate relationships, professional identity, and purpose. Each student’s reflections demonstrated growth in these areas as a direct result of participating in the course. Students changed as writers because of the course, identified several andragogical techniques that enabled their success in the course, and grew in their professional identities as writers. Additionally, students mastered content and built a toolbox full of writing tools they can use as they progress through their education and become professionals. Extending the education and identity theory into writing education models and writing competency models would provide a unique aspect of the role students’ self-perceived identity plays in their abilities to produce text.
Keywords: Writing; writing-intensive course; education and identity